Faktor Risiko Status Gizi Kurang Pada Balita Di UPT Puskesmas Desa Lalang - Dian Lestari Maizs; Zuraidah Nasution; Rapida Saragih (Universitas Respati Indonesia, 2020)
Based on Nutritional Status Monitoring (PSG) from the Ministry of The health of the Republic of Indonesia, malnutrition status in children under five according to Body Weight (BB) / Age (U) is 18.4%. For the city of Medan in 2017 the nutritional status of under-fives was 6.0%. This study aims to analyze the risk factors for malnutrition in children under five in the Village Lalang Village Health Unit in 2018. The type of study used case-control. The sample of this study was 30 mothers who had children under five who experienced malnutrition (case) and 30 mothers who had children under five did not experience poor nutrition (control) in Health Centre Unit Office Desa Lalang, Medan. Data were analyzed by conducting Chi-square analysis and logistic regression. The results of the study showed that from 5 research variables only 3 variables affected underweight status in toddlers at the Lalang Village Health Centre Medan in 2018, namely knowledge about nutrition (sig 0.001 OR 15,776), family income (sig 0.004 OR 12,382), and history of infection (sig 0.014 OR 7,767). It is recommended for mothers of children under five to provide more nutritious food and enough energy for their children, in the posyandu every month to monitor the growth and development of children under five and be more active in seeking information about toddlers nutrition through counselling by health workers.